RESIDENTIAL RENEWABLE ENERGY: BY WHOM? (Utah Environmental Law Review; Vol 31 No 2 (2011))
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} President Obama's 2011 State of the Union speech termed development of clean energy sources our "Sputnik Moment," and called for 80 percent of the nation's electricity to be generated from renewables, clean coal, and nuclear power by 2035. The Sputnik metaphor is less than ideal, because it confuses the issue by introducing a security dimension with no direct parallel to the present situation. However, the president's message is clear: we need research, development and deployment of a new generation of energy technologies. As the president put it, "We're telling America's scientists and engineers that if they assemble teams of the best minds in their fields, and focus on the hardest problems in clean energy, we'll fund the Apollo projects of our time." The president's focus on the technology of renewable energy, however, is an indicator that a deceptively difficult question remains less well addressed: how can we overcome the built-in barriers of the current electricity infrastructure and create the distribution system that will bring renewable energy to American homes? The technology already exists to put solar photovoltaic (PV) panels on millions of homes, but we have paid inadequate attention to getting them there. This current lack of focus on distribution will limit residential solar deployment indefinitely, unless it is addressed soon.